Design of Automated Processing Equipment Shallots (PEBMO) To Improve Product Quality Shallots - Indrawati, Elsanda Merita; Munawi, Hisbulloh Ahlis; Suwardono, Agus; Santoso, Rachmad (International Journal for Educational and Vocational Studies, 2019)
For farmers onion, red onion quality is required to be maintained and prioritized, as the quality affect the selling price in the market. There are three types of quality of onion, which is of high quality red onion, red onion, medium quality and low quality onion. The third quality of onion was always found in every harvest, only a percentage of each crop are changing in every quality. Onion have lower quality will have a selling price is also very low, this has resulted in farmers losing money if yields lower quality onions have a high percentage. The best way to overcome the loss factor is to cultivate the red onion into a low-quality food products of high quality, so for that tool "PEBMO" is a solution to overcome the problems of onion farmers. Tools "PEBMO" designed to be able to make high quality products fried onions. This tool is designed to have 3 working system, ie peeler onion, red onion chopper, and oil drainer. With the tool "PEBMO" farmers can cultivate shallots low quality products easily and quickly, because farmers do not need to be difficult to peel and chop the onion using the manual method. In addition the tool is equipped with a tool that prevents the oil drainer fried onion products are completely free of oil and durable. Besides these tools also make fried onion products more hygienic and healthier because they have low levels of oil content. So with the "PEBMO" can improve the quality of low red onion into food products with high quality and price.